2018–2019 Florida Citrus Production Guide: Rootstock and Scion Selection - Ute Albrecht; Fernando Alferez; Mongi Zekri (EDIS, 2019)
This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Ute Albrecht, Fernando Alferez, and Mongi Zekri, and published by the Horticultural Sciences Department, July 2018.